DIALEKTIKA PERLINDUNGAN HUKUM BAGI GURU DALAM MENDISIPLINKAN SISWA DI SEKOLAH - Fokky Fuad; Istiqomah Istiqomah; Suparji Achmad (Universitas Muhammadiyah Tangerang, 2020)
Teachers as educators are often in a dilemmatic position, between the demands of the profession and community treatment. Teachers are required to be able to deliver students to achieve educational goals. However, when teachers try to punish students in order to enforce discipline. spontaneously parents and society categorize it as an act that violates human rights and child protection laws. The formulation of the problem in this study are: First, how to protect the rights of teachers in disciplining students? Second, Has the Court Decision related to the teacher's efforts to discipline students provided protection for teachers or vice versa? The research method used is to use the normative legal method. The theoretical framework used is to use the theory of legal protection developed by Satjipto Rahardjo. The conclusions generated in this study: First, in the context of the dialectics between norms that meet each other, a legal synthesis appears through the presence of the Supreme Court's Decision which is able to provide protection for teachers. Second, that the Supreme Court Decree No. 1554 K / PID / 2013 has been able to provide optimal protection for teachers to carry out their functions as educators.